2000
DOI: 10.1001/archfami.9.6.533
|View full text |Cite
|
Sign up to set email alerts
|

How Often Do Office Blood Pressure Measurements Fail to Identify True Hypertension?: An Exploration of White-Coat Normotension

Abstract: Office measures of BP lack sensitivity, missing a sizable portion of individuals who have hypertensive mean ABP measurements. Subjects with WCN differ from true normotensive subjects on several demographic and lifestyle variables. Only those office readings averaging 20 points above or below the 140/90 cutoff represent safe diagnostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 26 publications
6
87
0
1
Order By: Relevance
“…A study of 319 subjects that applied a battery of tests for anxiety, depression, stress, disappointment, hostility and social support showed no difference between masked hypertensives and normotensives. 14 The MMPI-2 type-A scale questionnaire that was used in this study to evaluate the personality type has been proven to predict coronary heart disease incidence in a cohort of disease-free individuals. 18 The results showed masked hypertensives to be less of type-A personality, meaning that they were less hard-driving, fast-moving and work-oriented compared with white coat or sustained hypertensives that were more impatient and irritable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 319 subjects that applied a battery of tests for anxiety, depression, stress, disappointment, hostility and social support showed no difference between masked hypertensives and normotensives. 14 The MMPI-2 type-A scale questionnaire that was used in this study to evaluate the personality type has been proven to predict coronary heart disease incidence in a cohort of disease-free individuals. 18 The results showed masked hypertensives to be less of type-A personality, meaning that they were less hard-driving, fast-moving and work-oriented compared with white coat or sustained hypertensives that were more impatient and irritable.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, scant attention has been placed on psychological parameters, such as daily stress, hostility, anger, depression and social support. 14 The aim of this study was to investigate potential characteristics related with the occurrence of MH and to compare the cardiovascular status of these subjects with white coat and sustained hypertensives.…”
Section: Introductionmentioning
confidence: 99%
“…Whether young age is a consistent feature of MH is a matter of some disagreement (11,14,24,25), with some reports not finding this association.…”
Section: Who Should Be Tested For Mh?mentioning
confidence: 99%
“…In addition to the factors mentioned by the European Society of Hypertension (23), other characteristics of MH have been identified: obesity (12)(13)(14)(15); impaired baroreflex sensitivity (20); current or past smoking (14,22,25); increased serum creatinine levels (14); increased urinary albumin excretion (16); high heart rate (24); and increased alcohol consumption (22,25). Although the list is becoming quite long, these factors, taken together, can lead one to suspect MH in a higher risk patient who may be expected to have BP readings in the hypertensive range.…”
Section: Who Should Be Tested For Mh?mentioning
confidence: 99%
“…20 The exact prevalence of MHT was achieved with the introduction of ABPM that showed a diagnostic sensitivity higher than home BP monitoring (HBPM). 21 Indeed analysis from PAMELA reported a prevalence of 9%; 22 other studies reported frequencies ranging from 10.2% 23 to 23%, 24 reaching even 48%. 25 It might be fair to say that since the WCHT is more common in the elderly, consequently MHT should gradually decline with age.…”
mentioning
confidence: 95%